Apparent Violations Of The Final-Over-Final Constraint: The Case Of Gbe Languages - Aboh, Enoch (My University, 2020)
In a series of recent talks and articles, Theresa Biberauer, Anders Holmberg, Ian Roberts, and Michelle Sheehan argue that the final-over-final condition (FOFC) is an absolute universal regulating structure building. Yet, many languages deviate from FOFC thus suggesting that this condition is not “surface-true”. The question therefore arises what factors make languages violate FOFC on the surface. In order to answer this question, we need a typology of FOFC-violating languages, as well as a detailed description of such violations. In this short essay, I describe FOFC violations in Gbe and some creoles, while relating the observed phenomena to some theoretical questions they raise.
Keywords: Gbe languages; final-over-final condition; violations